British financial, managerial and technical assistance in establishing the global shipbuilding giant, Hyundai Heavy Industries. (February 2016) - Kang, J Y; Kim, Song; Murphy, Hugh; Tenold, Stig
The aim of this article is to present the early history of Hyundai Heavy Industries, currently the world's largest shipbuilder. The company was established by the prolific South Korean entrepreneur Chung Ju-Yung in the early 1970s. Due to limited experience in shipbuilding, the establishment relied heavily on foreign assistance. This article sheds new light on the crucial relationship between Chung and two British companies: the Newcastle-upon-Tyne-based consulting firm A&P Appledore International Limited, and the Lower Clyde shipbuilders Scott Lithgow Limited, during the beginnings of large-scale South Korean shipbuilding. The article is based on a combination of British and South Korean archival sources, as well as secondary literature and the oral and written testimony of consultants and workers involved in the project.